Efficacy and safety outcomes of single-agent ibrutinib therapy in chronic lymphocytic leukemia and relapsed/refractory mantle-cell lymphoma - Pınar, İbrahim Ethem and Ozkocaman, Vildan (The European Research Journal, 2023)
Objectives: We aimed to evaluate patients using ibrutinib for the treatment of chronic lymphocytic leukemia (CLL) and relapsed/refractory mantle-cell lymphoma (MCL), focusing on high-risk subgroups, predictors of efficacy, response levels, and safety profile. Methods: This retrospective cohort study included adult patients diagnosed with CLL and relapsed/refractory MCL who were started on ibrutinib as a single-agent between May 2015 and December 2021 in Bursa Uludag University, Department of Hematology. Results: Of the 45 patients (23 CLL, 22 MCL) started on ibrutinib, the median age was 65 (range: 48-86) years, and 66.7% were male. Del(17p) was present in 47.8% of CLL patients; there was no remarkable difference between del(17p) status and the rates of achieving CR. The median follow-up with ibrutinib treatment in CLL patients was 13.3 (range: 0.3-77.8) months. In univariate analysis, progression-free survival (PFS) and overall survival (OS) were associated with the advanced Eastern Cooperative Oncology Group (ECOG) score (p = 0.003 and p = 0.004, respectively), and > 2 lines treatment regimens before ibrutinib (p = 0.016 and p = 0.050, respectively). In multivariate analysis, the ECOG performance status remained significant for OS. The median use of ibrutinib for MCL patients was 6 (range: 1-48) months, and the proportion of patients who achieved CR was 27.3%. In the univariate analysis of MCL patients, the ECOG performance status for PFS and OS was statistically significant (p = 0.045 and p = 0.016, respectively). Patients’ most common non-hematological adverse events were pneumonia and urinary tract infection. Conclusions: Our investigation of patient outcomes treated outside clinical trials confirms ibrutinib’s sufficient efficacy and safety profile in CLL and relapsed/refractory MCL.